Monitoring the grasslands of the Sahel using NOAA AVHRR data: Niger 1983 - Justice, C.O.; Hiernaux, Pierre H.Y. (Informa UK Limited, 1986)
Compares normalized difference vegetation index data derived from the advanced very high resolution radiometer on board the NOAA-7 satellite for the 1983 growing season for the saheliant zone of Niger wit biomass estimates derived from an emperical grassland productivity model.